2021
DOI: 10.1042/cs20210579
|View full text |Cite
|
Sign up to set email alerts
|

Fifty years of research on the brain renin–angiotensin system: what have we learned?

Abstract: Although the existence of a brain renin–angiotensin system (RAS) had been proposed five decades ago, we still struggle to understand how it functions. The main reason for this is the virtual lack of renin at brain tissue sites. Moreover, although renin’s substrate, angiotensinogen, appears to be synthesized locally in the brain, brain angiotensin (Ang) II disappeared after selective silencing of hepatic angiotensinogen. This implies that brain Ang generation depends on hepatic angiotensinogen after all. Rodrig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Further, it has been revealed that Ang II binds to AT1R and AT2R in neurons, astrocytes, oligodendrocytes, and microglial cells [6,51]. These data confirm the existence of a local RAS in the brain that is involved in water and sodium homeostasis and the regulation of cerebral blood flow [52]. However, chronic activation of the brain RAS and subsequently elevated levels of Ang II also induce pathophysiological conditions such as neuroinflammation, oxidative stress, and age-related diseases [53].…”
Section: Brain Ras Components: From Physiology To Pathologymentioning
confidence: 67%
“…Further, it has been revealed that Ang II binds to AT1R and AT2R in neurons, astrocytes, oligodendrocytes, and microglial cells [6,51]. These data confirm the existence of a local RAS in the brain that is involved in water and sodium homeostasis and the regulation of cerebral blood flow [52]. However, chronic activation of the brain RAS and subsequently elevated levels of Ang II also induce pathophysiological conditions such as neuroinflammation, oxidative stress, and age-related diseases [53].…”
Section: Brain Ras Components: From Physiology To Pathologymentioning
confidence: 67%
“…For example, a single-nucleus RNA sequencing study revealed that choroid plexus epithelial express high levels of components from the renin angiotensin system [ 106 ••]. Considering that brain expression of renin is low [ 107 ], this recent discovery of renin-expressing cells in the choroid plexus [ 106 ••] could support the local production of Ang II in the brain. Filling the known and yet-to-be-identified knowledge gaps will be critical for mitigating the deleterious effects of CVD on a global scale.…”
Section: Discussionmentioning
confidence: 99%
“…Considering our previous work emphasized the role of RAS in the development of tissue injuries and the inhibitory effects of vitamin D on overactivity of tissue RAS, we attempted to uncover the underlying molecular mechanisms involved in the protection of vitamin D in COVID-19 patients from CNS damages on the aspect of brain RAS, which has been proposed five decades ago [87]. Human studies on the postmortem brain revealed that human coronavirus variants and SARS-CoV-2 could infect neurons and glia, demonstrating that SARS-CoV-2 may have similar neurovirulence [77].…”
Section: Mechanism Studiesmentioning
confidence: 99%
“…Furthermore, the research data showed the expression of ACE2 in neuronal and glial cells [89], which are also potentially vulnerable to SARS-CoV-2 infection. Attractively, a few studies have demonstrated the existence of RAS components in the basal ganglia, and particularly in the nigrostriatal system [90], even in mitochondria of dopaminergic neurons [91], though there are still controversial opinions about the presence of brain RAS as the angiotensin generation in the brain is concerned [87,92].…”
Section: Mechanism Studiesmentioning
confidence: 99%